Imunoexpressão das caderinas E e N em carcinomas gástricos primários e respectivas metástases linfonoidais - Rodrigues, Bruno Jucá (2014)
E - Cadherin and N - cadherin are calcium - dependent adhesion molecules with important roles in the shaping and maintenance of normal tissue architecture and are altered in several types of cancer, according to the biomedical literature. The aim of this study is to evaluate the expression of both proteins in gastric carcinoma and their ly mph node metastases as well as their possible participation in tumor progression. Fifty - one (51) cases of gastrectomy for gastric carcinoma were used, 35 of which with available lymph nodes, obtained from the files of the Department of Pathology and Forensic Medicine, Federal University of Ceará (DPML / UFC). The cases were classified into intestinal (26) and diffuse (25) types according to Lauren's classification (1965). Data associated with tissue microarray immunohistochemistry wi th monoclonal antibody anti - E - cadherin and N - cadherin, anti - universal detection and strepta vidin - biotin - peroxidase system were used. The expression of E - cadherin was evaluated according to the following scores (based on previous reports): preserved when pr esence of E - cadherin membrane was found in 50% or more of tumor cells, and decreased when less than 50% of these cells showed immunostaining. Labeling of N - ca dherin was considered positive when 5% or more of tumor cells presented with membrane and / or cyt oplasm stained by this protein, and negative when less than 5% of cells were marked. Expression preserved and reduced to E - cadherin, positive and negative N - cadherin for each histotype carcinoma, primary seat, lymph node, intestinal metaplasia and normal t issue distant from the tumor were compared. It was found that E - cadherin in greater than 5 centimeters tumors showed a significant reduction in the expression ( p = 0.0006). E - cadh erin was significantly reduced ( p = 0.0209) in diffuse carcinomas compared to normal mucosa distant from the tumor . The re were significant differences in the N - cadherin expression between normal and metaplastic epithelial cells in the basal third ( p <0.0001) and intermediate ( p = 0.0026 .In normal tissue, there was an increased neg ativity from basal (less differentiated) to superficial (more differentiated) epithelial levels. It was evident that in the primary tumor (92%), lymph node (100%) and intestinal metaplasia (100%) the negativity is predominant, whereas i n the normal tissue the positivity of N - cadherin occurre d in 74% of cases. The distribution of N - cadherin expression in mononuclear stromal cells had a similar positivity between primary tumor and lymph node metaplasia, while in lymph nodes occurred marked lacking of expression, with 92% of negative expression.